Etidronate as A Weak Chelating Agent on Root Canal Dentin: An Update Review - Samah Samir Bedir; Hossam Mossa; Ahmed Mohammed Hassan (Journal of Clinical and Diagnostic Research, 2017)
Successful root canal treatment depends on proper biomechanical cleaning and shaping of root canal system followed by threedimensional obturation. Irrigation solutions and chelating agents are used during root canal treatment to assist in smear layer removal and enhanced bonding with sealer. Different chelating agents are used in combination with irrigation solutions such as Ethylenediaminetetraacetic Acid (EDTA), Citric Acid (CA), mixture of doxycycline, citric acid and a detergent {Tween 80 (MTAD)}, chitosan, maleic acid and etidronate. Etidronate is a weak biocompatible chelating agent effective in smear layer removal with less harmful erosive effects on root canal dentin, compared with other strong chelating agents like EDTA and citric acid. Etidronate can be mixed with Sodium Hypochlorite (NaOCl) without interfering with its antimicrobial or dissolving activity while EDTA retains its calcium-complex when it is mixed with NaOCl reducing its tissue dissolving capacity.